Weight minimization of structural components reinforced with fiber-mat = Optymalne projektowanie lekkich elementów konstrukcyjnych wzmacnianych matami włókienniczymi - Wiśniewski, Jacek; Dems, Krzysztof (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The results of investigation in the area of designing of lightweight composite structures are presented. The thin, two-dimensional and linearly elastic disk reinforced with fibermat and subjected to service loading is considered.
Keywords: tarcza kompozytowa; kompozyt; maty włókiennicze; lekkie elementy konstrukcyjne; projektowanie optymalne; composite disk; fiber-mat; optimal design; evolutionary algorithms